THE RELATIONSHIP BETWEEN TEACHER'S ICT COMPETENCE AND CHILDREN'S DIGITAL LITERACY SKILLS IN KINDERGARTEN SURABAYA - Herawati, Herawati; Rinakit Adhe, Kartika; Dorlina Simatupang, Nurhenti; Khotimah, Nurul (Jurnal Pendidikan Anak, 2024)
This study aims to determine how the relationship between teacher ICT competence and children's digital literacy skills in kindergarten Surabaya. This research is a type of survey research with a quantitative approach. The data collection technique used was a questionnaire. The sample used in this study was kindergarten teachers who teach children aged 3-6 years, totaling 98 teachers. Data were analyzed using SPSS 29 for testing analytical requirements, inferential and hypothesis testing. Based on the results of this study, it can be concluded that there is a correlation and positive influence of teachers' ICT competence on children's digital literacy skills in kindergarten Surabaya. This is indicated by the Sig value < 0.05. The correlation and regression test results in the study were 0.001 < 0.05. The results of the regression equation in the study interpret that if the teacher's ICT competency variable increases by 1%, there will also be an increase in the digital literacy ability variable of kindergarten children by 0.800. This proves that it is important for teachers to improve ICT competencies to maximize early childhood digital literacy skills.